Possible Solutions for Outer Space Norm-Making - Kotzé, Theunis (South African Yearbook of International Law)
In the first instalment of this article, the author examined why the United Nations Committee for the Peaceful Uses of Outer Space (UN and UNCOPUOS), established to make international law of outer space, stopped making outer space treaties, and how did the International Institute for the Unification of Private Law (Institute International pour l’unification du Droit Privé or UNIDROIT), a non-UN entity established to unify private law, created with its 2012 Protocol to the Convention on International Interests in Mobile Equipment on Matters Specific to Space Assets (Space Protocol) what is allegedly the first outer space treaty in (then) thirty-two years. The UNCOPUOS system of public international law treaty-making was compared with the UNIDROIT private international law one; and the question as to whether the UNIDROIT has created a new method of treaty-making. The author now advances recommendations for the UNCOPUOS to produce hard law to cure this unsatisfactory situation. He concludes that the Space Protocol can only form part of space law if one accepts a fourth stage of development of space law as part of a redefining of space law sensu lato, and although multilateral treaty-making is no longer the most appropriate tool for meeting the new needs and requirements, treaties cannot be ignored in international space legislation.